Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13116181
|View full text |Cite
|
Sign up to set email alerts
|

BIM for Smart Hospital Management during COVID-19 Using MCDM

Abstract: In context of the recent COVID-19 pandemic, smart hospitals’ contributions to pre-medical, remote diagnosis, and social distancing has been further vetted. Smart hospital management evolves with new technology and knowledge management, which needs an evaluation system to prioritize its associated criteria and sub-criteria. The global effect of the COVID-19 pandemic further necessitates a comprehensive research of smart hospital management. This paper will utilize Analytical Hierarchy Process (AHP) within Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
(78 reference statements)
0
17
0
Order By: Relevance
“… Kumar et al (2021) identified and prioritized risk mitigation strategies for perishable food supply chains during the pandemic. Lin et al (2021) researched a hospital evaluation system and performed smart asset categorization in the COVID-19 context. Manupati et al (2021) analyzed health care waste disposal techniques for the effective treatment of medical wastes during COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Kumar et al (2021) identified and prioritized risk mitigation strategies for perishable food supply chains during the pandemic. Lin et al (2021) researched a hospital evaluation system and performed smart asset categorization in the COVID-19 context. Manupati et al (2021) analyzed health care waste disposal techniques for the effective treatment of medical wastes during COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A smart hospital is a concept that uses emerging technologies of information and communications technology (ICT) to optimize and manage the health care operations and its functional requirements efficiently [ 30 ]. Smart hospitals fall under the safety-critical domain as the safety of patients is at most priority.…”
Section: Performance Evaluation Of the Proposed Architectural Modelmentioning
confidence: 99%
“…For the past 18 months, numerous researches have been published to contribute to the fight against the pandemic. Early warning, rapid detecting, and diagnosis systems based on artificial intelligence are reported in [4][5][6][7][8]. Tracking and predicting models are reported in [9].…”
Section: Related Workmentioning
confidence: 99%